2019
DOI: 10.1175/jcli-d-18-0839.1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Spring and Summer Large-Scale Environments Associated with Mesoscale Convective Systems over the U.S. Great Plains

Abstract: Mesoscale convective systems (MCSs) are frequently observed over the U.S. Great Plains during boreal spring and summer. Here, four types of synoptically favorable environments for spring MCSs and two types each of synoptically favorable and unfavorable environments for summer MCSs are identified using self-organizing maps (SOMs) with inputs from observational data. During spring, frontal systems providing a lifting mechanism and an enhanced Great Plains low-level jet (GPLLJ) providing anomalous moisture are im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(172 citation statements)
references
References 45 publications
9
162
0
1
Order By: Relevance
“…In April, MCSs produced under strong baroclinic forcing usually feature broad stratiform rain region, which results in the largest precipitation area, but the number is relatively low compared to the midsummer, when the CONUS has the weakest baroclinic instability and minimal frontal forcing. However, due to the favorable thermodynamic conditions and possible influence from sub-synoptic disturbances, local convection can nevertheless frequently grow upscale into MCSs (Wang et al 2011;Song et al 2019;. The combination of spring-like baroclinic waves and a continuously warming surface possibly favors the peak number of MCSs in late spring and early summer (i.e., June), but the MCS precipitation areas are generally smaller than in spring.…”
Section: Evaluation Of Gpm's Capability In Mcs Detectionmentioning
confidence: 99%
“…In April, MCSs produced under strong baroclinic forcing usually feature broad stratiform rain region, which results in the largest precipitation area, but the number is relatively low compared to the midsummer, when the CONUS has the weakest baroclinic instability and minimal frontal forcing. However, due to the favorable thermodynamic conditions and possible influence from sub-synoptic disturbances, local convection can nevertheless frequently grow upscale into MCSs (Wang et al 2011;Song et al 2019;. The combination of spring-like baroclinic waves and a continuously warming surface possibly favors the peak number of MCSs in late spring and early summer (i.e., June), but the MCS precipitation areas are generally smaller than in spring.…”
Section: Evaluation Of Gpm's Capability In Mcs Detectionmentioning
confidence: 99%
“…Observational studies have documented various large-scale environment features important to MCS genesis, such as a low-level jet (LLJ) of air with low static stability and high convective available potential energy (CAPE), baroclinic frontal zone, vertical wind shear, low-level convergence and upper-level divergence (Coniglio et al 2010;Laing and Fritsch 2000;Song et al 2019). It is unclear if climate models, either global or regional scale, are able to simulate the diverse large-scale environmental conditions that are associated with observed MCSs in different seasons (Song et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the MMF with the coarse host‐GCM grid is able to capture MCSs in the Tropics (Tao & Chern, ; Randall et al, ). However, our study shows the MMF model has difficulty in simulating MCS‐associated precipitation in midlatitude continental conditions during spring where most MCSs were supported by strong baroclinic forcing (Feng et al, ; Song et al, ). The different model behaviors reflect the different mechanisms driving the MCSs between tropical and midlatitude regions.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…Investigating how resolving topography variations within the CRM domains would help the MMF model simulate MCSs can be an interesting future work. Further, summer MCSs in this region often occur under weak baroclinic forcing with favorable thermodynamic environments (Feng et al, ; Song et al, ). Future work similar to this study is needed to examine how well the MMF can simulate observed summer MCSs.…”
Section: Summary and Discussionmentioning
confidence: 99%